Mutual intelligibility of a Kurmanji and a Zazaki dialect spoken in the province of Elazig, Turkey - Ozek, Fatih; Saglam, Bilgit; Gooskens, Charlotte (Walter de Gruyter Gmbh, 2023)
We present the first results of a large project concerned with the mutual intelligibility between Zazaki and Kurmanji dialects spoken in Eastern Anatolia. There is an ongoing debate on the classification of Kurmanji and Zazaki as separate languages or as dialects of the same language, Kurdish. However, there is no scientific study of how well speakers of Zazaki and other dialects of Kurdish can understand each other. In this paper, we present the results of a pilot investigation where we tested the mutual intelligibility of 69 Kurmanji and Zazaki participants by means of a word translation task and asked the participants to estimate how well they could understand the other language variety. The results showed that overall the mutual intelligibility was rather low. There was a significant interaction between the effects of gender and language. Zazaki males identified more words correctly than Kurmanji males while Kurmanji females had higher intelligibility scores than Zazaki females. We suggest linguistic (lexical) and non-linguistic (attitudes and amount of exposure) explanations for the intelligibility results. We also have a closer look at the intelligibility of individual words to gain a greater understanding of the reasons for the asymmetric intelligibility results.
Keywords: Kurdish; Kurmanji; mutual intelligibility; translation task; Zazaki